The growth of Arthrospira platensis in spent medium - Noor Syida Md. Hassan.
Arthrospira platensis is an attractive microalgae used widely in food, pharmaceutical, cosmetics industries and other high-value cell components. In cultivation, a major component in the cost of production is the cost of nutrient. In this work, A. platensis was cultured in two phases of growth. In phase I, A. platensis was grown in freshly prepared medium. In phase II, spent medium was used as culture medium. There were highly difference in the growth performance and status of nutrient particularly N and P in the both phases of culture. The maximum growth occurred on day 12 for both phases of culture. The differences of biomass, chlorophyll a content and culture's optical density between the two phases of culture were 564 mg/L, 3.369 mg/L and 1.056 respectively. A. platensis cultured in phase I performed better growth. In freshly prepared medium, total N decreased from 7.648 ± 0.095 mg/L on day 0 to 5.637 ± 0.088 mg/L on day 16. In spent medium, it declined from 5.637 ± 0.088 mg/L on day 0 to 3.392 ± 0.0769 mg/L on day 16. Whereas, P in freshly prepared medium decreased from 3.677 ± 0.0769 mg/L to 1.829 ± 0.197 mg/L on day 16. In spent medium, it reduced from 1.829 ± 0.197 mg/L to 0.489 ± 0.045 mg/L on day 16. The use of spent medium significantly affect the growth of A. platensis.